Salivary AMY1 Copy Number Variation Modifies Age-Related Type 2 Diabetes Risk. (26th April 2020) - Liu, Yuwei; Smith, Caren E; Parnell, Laurence D; Lee, Yu-Chi; An, Ping; Straka, Robert J; Tiwari, Hemant K; Wood, Alexis C; Kabagambe, Edmond K; Hidalgo, Bertha; Hopkins, Paul N; Province, Michael A; et al.
Abstract: Background: Copy number variation (CNV) in the salivary amylase gene ( AMY1 ) modulates salivary α-amylase levels and is associated with postprandial glycemic traits. Whether AMY1 -CNV plays a role in age-mediated change in insulin resistance (IR) is uncertain. Methods: We measured AMY1 -CNV using duplex quantitative real-time polymerase chain reaction in two studies, the Boston Puerto Rican Health Study (BPRHS, n = 749) and the Genetics of Lipid-Lowering Drug and Diet Network study (GOLDN, n = 980), and plasma metabolomic profiles in the BPRHS. We examined the interaction between AMY1- CNV and age by assessing the relationship between age with glycemic traits and type 2 diabetes (T2D) according to high or low copy numbers of the AMY1 gene. Furthermore, we investigated associations between metabolites and interacting effects of AMY1 -CNV and age on T2D risk. Results: We found positive associations of IR with age among subjects with low AMY1 -copy-numbers in both studies. T2D was marginally correlated with age in participants with low AMY1 -copy-numbers but not with high AMY1 -copy-numbers in the BPRHS. Metabolic pathway enrichment analysis identified the pentose metabolic pathway based on metabolites that were associated with both IR and the interactions between AMY1- CNV and age. Moreover, in older participants, high AMY1 -copy-numbers tended to be associated with lower levels of ribonic acid, erythronic acid, and arabinonic acid, all of which were positively associated with IR. Conclusions: We found evidence supporting a role of AMY1 -CNV in modifying the relationship between age and IR. Individuals with low AMY1 -copy-numbers tend to have increased IR with advancing age.